Nano ski wax, effects and benefits - Haaland, N. H. (2013)
The effects of the gliding properties of ski waxes are often discussed and many speculations and assumptions are made. However there are not many studies and documented results in this field. This project is carried out in cooperation with Olympiatoppen and the Norwegian ski team to research and document the effects and benefits of gliding waxes. Ski base material consists of ultra-high molecular weight polyethylene (UHMWPE) in semicrystalline state. The focus will be on the material changes caused by the waxing process. This project examines two different types of ski base material with three different gliding waxes. Essential factors of the friction and the effects of gliding wax on skis were studied. The Fluor content, both in the base material and in the wax, and the Gallium content in one of the gliding waxes, was, given special attention. Experiments on the ski base materials, with and without waxes, were conducted. Material characterisation has been evaluated by using XPS, ICP and contact angle measurement of water droplets on the ski base materials. The friction properties have been tested with outdoor gliding field tests where the two ski bases have been compared with each other and also a reference ski. A tribometer was used in the lab to measure the coefficient of friction. The content of the ski base material were unknown, there is found that both type of bases tested contains Fluor. It was also found that the Fluor content on the top surface is not directly comparable with the surface energy and the contact angle.